2019
DOI: 10.1186/s12968-019-0566-z
|View full text |Cite
|
Sign up to set email alerts
|

Fast self-navigated wall shear stress measurements in the murine aortic arch using radial 4D-phase contrast cardiovascular magnetic resonance at 17.6 T

Abstract: Purpose 4D flow cardiovascular magnetic resonance (CMR) and the assessment of wall shear stress (WSS) are non-invasive tools to study cardiovascular risks in vivo. Major limitations of conventional triggered methods are the long measurement times needed for high-resolution data sets and the necessity of stable electrocardiographic (ECG) triggering. In this work an ECG-free retrospectively synchronized method is presented that enables accelerated high-resolution measurements of 4D flow and WSS i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(36 citation statements)
references
References 30 publications
4
32
0
Order By: Relevance
“…These findings are in accordance with the WSS values in this study compared to previous findings from Stalder et al [12]. The first step of longitudinal visualization of the WSS via a 2D imaging method is feasible in a high quality, thus, now the application of 3D acquisitions, as described in [37], in a longitudinal study is needed. However, the previous publication by Stalder et al [12] showed that a 3D measuring method underestimates the WSS values in comparison to a 2D measuring method.…”
Section: Discussionsupporting
confidence: 92%
“…These findings are in accordance with the WSS values in this study compared to previous findings from Stalder et al [12]. The first step of longitudinal visualization of the WSS via a 2D imaging method is feasible in a high quality, thus, now the application of 3D acquisitions, as described in [37], in a longitudinal study is needed. However, the previous publication by Stalder et al [12] showed that a 3D measuring method underestimates the WSS values in comparison to a 2D measuring method.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, accelerated techniques are needed in order to assess arterial wall shear stress values in reasonable measurement times. In 2019, a radial PC MRI sequence was presented that uses self-navigation and retrospective cine reconstruction for 4D flow measurements in the murine aortic arch [ 79 ]. Due to the strong signal enhancement of blood and suppression of undersampling artifacts, a scan time reduction to 35 min, and high spatial resolution (100 µm isotropic) were achievable.…”
Section: The Role Of Shear Stress In the Development And Progressimentioning
confidence: 99%
“…These murine disease models are used to advance our mechanistic understanding of atherosclerosis—thus, there is a need to adapt these methods to the murine system. In 2019, our group presented a self-gated radial 4D flow MRI sequence that enabled high-resolution WSS measurements in 35 min [ 79 ]. However, combined measurements of both WSS and PWV are challenging since both parameters have different requirements for the temporal and spatial resolutions [ 76 ].…”
Section: Wss and Pwv Interact To Promote Plaque Growth And Vasculamentioning
confidence: 99%
See 2 more Smart Citations